Effects of eyestalk ablation, thoracic ganglion extract and gonad extract from 'spent spawners’on ovarian maturation in pond-reared shrimps, Penaeus monodon Fabricius - Har, Chan Hooi; Halim, A.S.; Siti-Sara, A.R. (Wiley, 1991)
Eyestalk‐ablated and non‐ablated pond‐reared Penaeus monodon Fabricius of two sizes (116·3 ± 2·8g and 67·9 ± 1·0g body weight (BW)) were injected with crude thoracic ganglion extract from 'spent spawners’(0·4mg/g and 1·0mg/g shrimp respectively). Controls (ablated and non‐ablated groups) received either equivalent amounts of crude muscle extract or crustacean saline. In another experiment, non‐ablatéd shrimps (67·4 ± 1·8g BW) were injected with crude gonad extract from 'spent spawners'. The controls received an equal volume of crustacean saline. Significant differences (P < 0·05) in the gonadosomatic index and the gonad index in relation to the carapace length were detected between eyestalk‐ablated and non‐ablated shrimps; the larger shrimps showing a greater difference following treatments with muscle and thoracic ganglion extracts. However, no significant differences (P > 0·05) were detected between the thoracic ganglion‐treated groups and the controls in either the eyestalk‐ablated or non‐ablated shrimps. Nor were significant differences (P > 0·05) observed between the gonad‐treated group and the control and between the two control groups receiving crustacean saline and crude muscle extract.